CORRELATION BETWEEN SOCIAL SUPPORT AND INDIVIDUAL COPING STRATEGY OF HYPERTENSION AT TAGOGAPU VILLAGE - MULYANA, HILMAN (Jurnal Kesehatan Bakti Tunas Husada: Jurnal Ilmu-ilmu Keperawatan, Analis Kesehatan dan Farmasi, 2017)
Background: The background of this research is the increased prevalence of chronic hypertensionIndonesia. So it needs patient's ability to control the disease in their life time. There were missperception between situation demand caused hypertension and the patient’s ability to cope with it. So itbecomes the major problem which needs some support in every sources.Purpose:The purpose of this study is to analyze correlation between the sources of social support fromspouses, family, fellow sufferers of hypertension and individuals coping strategy in self-managementof hypertension.Methods: The research method was analytical cross sectional study and the data analysis used chisquare test. Data collection used modified questionnairre from the previous research, such as socialsupport from Thai Family upport Scale for Elderly Parents (TPSS-EP), and individual coping strategiesfrom Halim (2014) which modified Lazarus’s Way of Coping (developed by Aldwin and Reverson in1987). This studyinvolved 126 respondents based on purposive sampling criteria.Results: The results of this study showed that there was relationship between social support andindividual coping strategy (ρ-value = 0.000). the most social support obtained from spouses (57,11%).Conclusions: The conclusion of thi research showed that social support was unfavorable to individualcoping strategy in hypertension patient in Tugopagu VillageRecommendation:The community nurses should give the intervention to reduce the stressor andsupport them to cope with it by giving some knowledge about: (1) alternative problem solving (2)problem solving action (3) seeking some support and help, and (4) seeking information